Komunikasi Interpersonal Mahasiswi Bercadar: Pola Interaksi dan Hambatan Komunikasi - Talalu, Taufik R; Novia, Reni; Nurdin; Meilani, Risky Nia; Umbo, Alfin (LPPM IAIN Sultan Amai Gorontalo, 2025)
The phenomenon of veiled female students in higher education is an important subject of study because it often gives rise to various social perceptions in campus interactions. This study aims to examine the interpersonal communication between veiled female students, non-veiled female students, and the opposite sex, as well as to identify the barriers that emerge in the communication process. This research employed a qualitative approach at the State Islamic Institute of Sultan Amai Gorontalo. Informants were selected using the snowball sampling technique. Data were collected through semi-structured interviews and observation, and were analyzed descriptively using a qualitative approach. The findings show that the interpersonal communication of veiled female students is contextual and adaptive. In interactions with non-veiled female students, communication tends to be carried out carefully in order to maintain comfort and avoid misunderstandings. Meanwhile, communication with the opposite sex tends to be more limited, conducted only when necessary, and oriented toward clear purposes. The barriers to communication include difficulties in interpreting facial expressions, unclear voice delivery, and differences in the interlocutors’ experiences.